Immunopathogenesis of erythema nodosum leprosum - Made Sanitca Indah; I Gusti Agung Ayu Dwi Karmila (Intisari Sains Medis, 2021)
Leprosy is a chronic granulomatous disease. Its etiology is caused by Mycobacterium leprae (M. leprae). This disease may affect the skin, however it also may affect peripheral nervous system and other organs. The immunologic mechanism of erythema nodosum leprosum (ENL) has not been fully understood. The ENL reaction is the reaction of deposition in immune complex in the blood vessels. Recent studies have reported the association of several immunological markers with leprosy reactions, but inconsistent results have been obtained. Neutrophils are considered a histologic feature of ENL, histologic examination of ENL skin lesions revealed a strong perivascular neutrophil infiltrate throughout the dermis and subcutis. Another thing to note is T lymphocytes. It has been showed that the T-cell counts in peripheral blood of ENL patients is higher. Other immunological processes that play a role in EL immunopathogenesis involve T-helper (Th) cells, T regulatory cells, B cells, and other cytokines.